Effect of wave boundary layer on hydrodynamic forces on small diameter pipelines. (1st October 2016) - Cheng, Liang; An, Hongwei; Draper, Scott; White, Dave
Abstract: Effect of wave boundary layer on hydrodynamic forces on small diameter pipelines is speculated in this paper. It is found that use of the recommended calculation methods in DNV-RP-F109 leads to unrealistic predictions of high specific gravity (SG) requirements for small diameter pipelines subject to wave loading. Potential reasons for such high SG requirements under wave loading are speculated based on existing knowledge and experimental evidence, and a way forward is proposed. It is suspected that the unrealistic predictions are because the calculation methods ignore wave boundary layer effects on hydrodynamic forces. Highlights: The appropriateness of DNV-RP-F109 for small diameter pipelines is examined. The wave boundary layers strongly affect the stability of small diameter pipelines. More research is needed on the effect of wave boundary layer on pipeline stability.